LITERATURE REVIEW: PERILAKU MENYIKAT GIGI PADA REMAJA SEBAGAI UPAYA PEMELIHARAAN KESEHATAN GIGI DAN MULUT - Purwaningsih, Endang; Aini, Aisya Syarifa; Ulfah, Siti Fitria; Hidayati, Sri (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2022)
Background: DMF-T of adolescent grup is 1.9. This number can figure out still does not meet the RAN target for Dental and Oral Health Services in 2020, namely the DMF-T index of 4.1 for all ages and the DMF-T index of 1.26 in the 12 year age group. Objective: This study aims to determine the form of adolescent behavior in brushing teeth. Methods: This study was a literature review using the method of searching for articles that have passed the publication process in 4 academic publications and full text databases, namely Google Scholar, PubMed, Proquest, and DOAJ published in the last 5 years 2016-2020 which can be accessed in full text in pdf and formats. scholarly. Conclusion: Some teenagers brush their teeth twice a day, but there are still teenagers who have not perform brushing behavior with the recommended frequency of brushing teeth. Teens tend to brush their teeth at night. However, there are some teenagers who have not paid attention to the time of brushing their teeth properly. Most adolescents use a combination technique and some use vertical techniques and female adolescents abroad tend to use dental floss as a supporting tool for brushing their teeth.